The role of the market in health systems responsiveness - Kimberly Lakin; Sumit Kane (Critical Public Health)
We critically interrogate the current conceptualisation of health systems responsiveness in light of ongoing political, economic, and health system transitions occurring in many low- and middle-income countries (LMICs), and call for a nuanced, contemporaneous, and expanded understanding of the concept. Drawing on key work on health economics and healthcare markets, we unpack the economic and health systems transitions that LMICs have experienced in the last two decades, specifically the shift towards neoliberalism. We discuss the impact of these transitions, particularly, the rapid growth in for-profit care and the covert or outright privatisation of public health services, on health care provision. We critically review the literature on health systems responsiveness to then demonstrate how current analytical frameworks do not yet sufficiently reflect the role of the market in responsive care provision. In light of this, we make a case for explicitly recognising the role of the market logic in both shaping peoples’ expectations of their health systems and the health system’s response to these expectations.